2015
DOI: 10.5489/cuaj.2377
|View full text |Cite
|
Sign up to set email alerts
|

Bone metastases affect prognosis but not effectiveness of third-line targeted therapies in patients with metastatic renal cell carcinoma

Abstract: Introduction: Treatment of metastatic renal cell carcinoma (mRCC) has improved with the use of targeted therapies, but bone metastases continue to be negative prognostic factor. Methods: Patients with mRCC treated with everolimus (EV) or sorafenib (SO) after two previous lines of targeted therapies were included in the analysis. Overall survival (OS) and progressionfree survival (PFS) were assessed based on the presence of bone metastases and type of therapy; they were also adjusted based on prognostic criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
3
5
0
Order By: Relevance
“…In addition, treatment response at week 8 by disease site was not prognostic for survival. This is in contrast to previous studies which have shown that bone and liver metastases are adverse independent prognostic factors for OS in metastatic RCC [16][17][18]. This correlates with findings from patients treated with cytokines where liver and bone metastases have been included as adverse factors in a prognostic model [19].…”
Section: Discussionsupporting
confidence: 73%
“…In addition, treatment response at week 8 by disease site was not prognostic for survival. This is in contrast to previous studies which have shown that bone and liver metastases are adverse independent prognostic factors for OS in metastatic RCC [16][17][18]. This correlates with findings from patients treated with cytokines where liver and bone metastases have been included as adverse factors in a prognostic model [19].…”
Section: Discussionsupporting
confidence: 73%
“…Iacovelli and colleagues have published an important analysis examining the role of bone metastases in prognosis and prediction of efficacy in the third-line setting. 1 This work confirms previous publications that bone metastases in mRCC are associated with a poorer overall survival. 2 However, the search for predictive markers that can help determine which agent is more efficacious for a particular patient remains elusive.…”
supporting
confidence: 82%
“…Finally, because axitinib is relatively new and not included in these studies, it is unknown how this newer VEGF inhibitor would compare. 1 Bone metastases are often difficult to treat in mRCC. Their response to targeted therapy is less satisfactory compared to other sites, such as lung metastases.…”
mentioning
confidence: 99%
“…Five of these studies have been excluded from this review because of the update of the scope excluding sunitinib as it is not recommended at second line in the most up-to-date ESMO guidance for RCC 12. Five new studies, one RCT and four retrospective chart reviews were identified in the update and extension searches (including terms for lenvatinib with everolimus) run in January 2018, making a total of 12 included studies 13–15 19 20 27–33…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies (n=5144) met the inclusion criteria (table 1): five RCTs (one double-blind28 and four open-label13 15 20 28) and seven observational studies19 27 29–33 (retrospective cohort studies). Sample sizes varied from 101 (HOPE 205)15 to 821 (CheckMate 025)14 participants.…”
Section: Resultsmentioning
confidence: 99%